2015
DOI: 10.1016/j.jbiotec.2014.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic production of itaconic acid in Synechocystis sp. PCC6803

Abstract: Here, we report the photosynthetic production of itaconic acid (IA), a promising building block, from carbon dioxide (CO₂) by Synechocystis sp. PCC6803. The engineered PCC6803 strain expressing cis-aconitate decarboxylase, the key enzyme in IA biosynthesis, produced 0.9 mg/L and 14.5 mg/L of IA at production rates of 42.8 μgL(-1)day(-1) and 919.0 μgL(-1)day(-1), under conditions of constant bubbling with air and 5% CO₂, respectively. This is the first report on the possibility of IA production from CO₂ via the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…PCC6803 [14]. The engineered PCC6802 strain expressing CAD enzyme produced 0.9 mg and 14.5 mg IA L −1 under conditions of constant bubbling with air and 5% CO 2 , respectively.…”
Section: Recombinant Microorganisms For Production Of Itaconic Acidmentioning
confidence: 99%
“…PCC6803 [14]. The engineered PCC6802 strain expressing CAD enzyme produced 0.9 mg and 14.5 mg IA L −1 under conditions of constant bubbling with air and 5% CO 2 , respectively.…”
Section: Recombinant Microorganisms For Production Of Itaconic Acidmentioning
confidence: 99%
“…The cadA gene is part of a gene cluster that also comprises a mitochondrial TCA transporter, a membrane permease and a transcription factor proposed to regulate pathway‐specific expression of cluster genes (Li et al ., ). The biochemical elucidation of itaconate production, including its genetic background, has led to a surge of metabolic engineering efforts in recent years with itaconate production established in several heterologous hosts (Kanamasa et al ., ; Li et al ., ; Blumhoff et al ., ; Klement and Büchs, ; Blazeck et al ., ; Huang et al ., ; Okamoto et al ., ; Chin et al ., ; Vuoristo et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Chin et al [51] reported the photosynthetic production of IA from CO 2 in a genetically engineered cyanobacterium (Synechocystis sp. PCC6803) by expressing cadA.…”
Section: Bottlenecks and Remediesmentioning
confidence: 99%